2012
DOI: 10.1186/2228-5547-3-5
|View full text |Cite
|
Sign up to set email alerts
|

A new colorimetric method for the determination of nifedipine tablets by derivatization using 4-carboxyl-2,6-dinitrobenzene diazonium ion

Abstract: Investigations were carried out to compare the effectiveness of compounds such as sodium nitrite, trisodium citrate (TSC) and TSC-zinc acetate to inhibit the corrosion of steel rebar in simulated concrete interstitial solution contaminated with chloride and to explain the mechanism of corrosion inhibition on reinforcing steel by these systems. Inhibition efficiency of these systems was studied by electrochemical techniques such as potentiodynamic polarization and half cell potential measurements. Electronic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The results showed that the titration value and colourimetric value for the ascorbic acid were consistent, indicating that each technique is appropriate for determining ascorbic acid. This result means that there was little or no interference of the excipient on the assay procedure [12]. Seven out of the nine brands were within the official titration specification of 95.0-107.50% BP (2018).…”
Section: Discussionmentioning
confidence: 78%
“…The results showed that the titration value and colourimetric value for the ascorbic acid were consistent, indicating that each technique is appropriate for determining ascorbic acid. This result means that there was little or no interference of the excipient on the assay procedure [12]. Seven out of the nine brands were within the official titration specification of 95.0-107.50% BP (2018).…”
Section: Discussionmentioning
confidence: 78%
“…Several study showed that validation and estimation of STZ may be done using high-performance liquid chromatography (HPLC) [4], high-performance thin layer chromatography (HPTLC) [5,6] colorimetric method after chemical derivatization [7,8], and UVspectrophotometric methods both in combination with ofloxacin or gatifloxacin or alone [9,10]. Absence of sufficient experimental data of UVspectrophotometric methods for quantitative estimations of satranidazole (STZ) in pharmaceutical formulation using different classes of solvents influence to perform the present study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully applied to the assay of many clinically useful drugs. The chemical derivatization methodologies are based on absorption spectroscopy [5][6][7][8][9][10][11][12][13][14][15][16] and liquid chromatography [17].…”
Section: Introductionmentioning
confidence: 99%